Research on the Biodiversity Assessment of Endangered Medicinal Flora within the Dubri Wildlife Sanctuary located in the Sidhi District of Madhya Pradesh, India - Mohammad Salim; Pradeep Kumar Dwivedi (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The current study focuses on numerous plant species observed within the Dubri Wildlife Sanctuary in Sidhi District, Madhya Pradesh, India. The research documents rare and endangered plant species found at the study site. The paper records 37 plant species as rare or endangered, providing their botanical names, local names, red data categories, and current status in the study area. Many of these plant species require immediate conservation efforts due to their critical status. The situation is concerning, with certain endangered species needing heightened attention. Additionally, the study underscores the importance of protecting some rare and endangered plants that are still abundant in the Dubri Wildlife Sanctuary of Sidhi district. Preserving them within their natural habitat in the forest area serves as an effective model for conserving plant diversity, especially considering the sanctuary’s significant role in safeguarding a substantial number of endangered and rare plants.